Method for synthesizing magnesium aluminate spinel powder based on flash Joule heat, magnesium aluminate spinel transparent ceramic and preparation method of magnesium aluminate spinel transparent ceramic

Through flash Joule thermal synthesis technology, the rapid heating and cooling are increased and cooled down, and the problems of high cost and complex synthesis of magnesium-aluminum spinel powder in the existing technology are solved, and the synthesis of high purity and small particle size is achieved, and the performance of magnesium-aluminum spinel transparent ceramics is improved.

CN119707477APending Publication Date: 2025-03-28SOLOMON (CHANGZHOU) ALLOY NEW MATERIAL CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411911418.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult to quickly synthesize high-purity and small particle size magnesium-aluminum spinel powders in the prior art, resulting in high preparation cost, complex process and environmental pollution of magnesium-aluminum spinel transparent ceramics.

Method used

Flash evaporation joule heat synthesis technology is used to quickly heat up, insulate and cool the mixed powder through the Joule heat generated by pulsed flash discharge to obtain magnesium aluminum spinel powder with a particle size as small as 40nm.

Benefits of technology

The rapid synthesis of high-purity and small particle size magnesium-aluminum spinel powder is achieved, which reduces preparation costs, simplifies the process, reduces environmental pollution, and improves the mechanical and optical properties of magnesium-aluminum spinel transparent ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707477A_ABST
    Figure CN119707477A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synthesizing magnesium aluminate spinel powder based on flash evaporation Joule heat, magnesium aluminate spinel transparent ceramic and a preparation method thereof.The method for synthesizing the magnesium aluminate spinel powder based on the flash evaporation Joule heat comprises the step that Joule heat generated by pulse flash evaporation discharge is used for heating mixed powder to obtain the magnesium aluminate spinel powder, the mixed powder comprises MgO powder and alpha-Al2O3 powder in a molar ratio of 1: (1-1.5), and the step of heating comprises discharge heating, heat preservation and cooling. According to the embodiment of the invention, joule heat is generated through pulse flash discharge, so that the raw material powder is rapidly heated and reacted, the synthesis time is short, the operation is simple, the energy consumption is low, and the pure-phase magnesium aluminate spinel powder with the particle size as small as about 40nm can be obtained and is used for preparing the magnesium aluminate spinel transparent ceramic; the mechanical property and the optical property of the magnesium aluminate spinel transparent ceramic are favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of advanced ceramic preparation, and in particular to a method for synthesizing magnesia-alumina spinel powder based on flash Joule heat, magnesia-alumina spinel transparent ceramics and a preparation method thereof. Background Art

[0002] Magnesium aluminum spinel transparent ceramics have good optical properties, with a theoretical transmittance of up to 87%, a transmission band between 0.19-7μm, covering the near-ultraviolet to mid-infrared band, and are optically isotropic materials. In addition to optical properties, magnesium aluminum spinel has many other excellent physical and chemical properties, such as a melting point of up to 2135℃, a low density (3.58g / cm 3 ), has high mechanical strength and hardness at room temperature and high temperature, good chemical corrosion resistance, good electrical insulation, relatively low thermal expansion coefficient, high thermal shock resistance, etc., so that it can be used in transparent armor, infrared transparent windows of missile launchers and reconnaissance pods, and transparent hoods of infrared search missiles and other military fields. In addition, it is also considered for a series of civilian fields, including: UV lithography windows, spacecraft, barcode scanners, watches, night vision systems, high-temperature eyepieces and laser igniters, etc.

[0003] Magnesium-aluminum spinel powder with high purity, fine particle size and high sintering activity is crucial for the preparation of magnesium-aluminum spinel transparent ceramics. Magnesium-aluminum spinel powder with high purity and fine grains is beneficial to the improvement of the optical and mechanical properties of magnesium-aluminum spinel transparent ceramics. At present, most researchers use magnesium-aluminum spinel powder produced by Baikowski Company of France as raw material. Although the prepared ceramics have good optical properties, they are expensive (about 2,600 yuan / kg), which will greatly increase the cost of use. In order to reduce costs, relevant personnel have carried out independent synthesis research on magnesium-aluminum spinel powder, but the synthesis method has many steps and complex processes. The synthesis process may produce harmful gases to pollute the environment. The powders synthesized by some methods have coarse particle sizes and are very time-consuming, with low production efficiency and high energy consumption.

[0004] In view of this, it is particularly necessary to develop a method for quickly synthesizing pure phase and fine-particle magnesium aluminate spinel powder and use it for the preparation of magnesium aluminate spinel transparent ceramics with good mechanical and optical properties. Summary of the invention

[0005] The purpose of the present invention is to provide a method for synthesizing magnesium aluminate spinel powder based on flash Joule heat, magnesium aluminate spinel transparent ceramics and a preparation method thereof, so as to prepare magnesium aluminate spinel powder with high purity and fine particle size, so as to obtain magnesium aluminate spinel transparent ceramics with good mechanical properties and optical properties.

[0006] The present invention is achieved in that:

[0007] In a first aspect, the present invention provides a method for synthesizing magnesium aluminate spinel powder based on flash Joule heat, comprising: heating a mixed powder using Joule heat generated by pulse flash discharge to obtain magnesium aluminate spinel powder, wherein the mixed powder comprises MgO powder and α-Al2O3 powder in a molar ratio of 1:(1-1.5), and the heating is followed by heat preservation and cooling.

[0008] In an optional embodiment, the heating, insulation and cooling cycles are performed 1-10 times;

[0009] And / or, the particle size of the MgO powder is below 100 nm and the purity is above 99.9%;

[0010] And / or, the particle size of the α-Al2O3 powder is below 100 nm and the purity is above 99.9%;

[0011] And / or, the preparation of the mixed powder includes: ball milling, mixing, drying and sieving MgO powder and α-Al2O3 powder in sequence to obtain the mixed powder.

[0012] In an optional embodiment, the medium for ball milling is anhydrous ethanol, the grinding balls are made of alumina, the mass ratio of the grinding balls to the mixed powder is (4.5-5.5):1, the mass ratio of the mixed powder to anhydrous ethanol is (0.2:0.8) to (0.3:0.7), the ball milling method is planetary ball milling, the rotation speed is 200 to 300 r / min, and the ball milling time is 20 to 30 hours;

[0013] And / or, the drying temperature is 50° C. to 80° C., the drying time is 8 h to 12 h, and the sieving mesh size is 150 meshes.

[0014] In an optional embodiment, the voltage of the pulse flash discharge is 200V to 300V, the temperature of the insulation step is 1200°C to 1600°C, the insulation time is 0.3s to 10s, and the heating rate is 1500°C / s to 4000°C / s.

[0015] In a second aspect, the present invention provides a method for preparing a magnesium-aluminum spinel transparent ceramic, comprising: molding, pressureless sintering, hot isostatic pressing and annealing the magnesium-aluminum spinel powder described in the aforementioned embodiment to obtain the magnesium-aluminum spinel transparent ceramic.

[0016] In an optional embodiment, the molding method is dry pressing and then cold isostatic pressing, wherein the pressure of dry pressing is 10MPa-20MPa, the holding time is 3min-6min, and the pressure of cold isostatic pressing is 200MPa-300MPa, and the holding time is ≥10min;

[0017] And / or, the molding method is gel injection molding followed by cold isostatic pressing, wherein the gel system used for gel injection molding has acrylamide as a monomer, methylenebisacrylamide as a cross-linking agent, ammonium persulfate as an initiator, and tetramethylethylenediamine as a catalyst; the cold isostatic pressing pressure is 200MPa to 300MPa, and the holding time is ≥10min.

[0018] In an optional embodiment, the pressureless sintering temperature is 1300° C. to 1550° C., and the time is 5 h to 15 h.

[0019] In an optional embodiment, the hot isostatic pressing is performed at a pressure of 150 MPa to 200 MPa, a temperature of 1350° C. to 1650° C., and a time of 2 h to 4 h.

[0020] In an optional embodiment, the annealing temperature is 1100° C. to 1300° C., and the holding time is 3 h to 6 h.

[0021] In a third aspect, the present invention provides a magnesium-aluminum spinel transparent ceramic prepared by the method described in any one of the aforementioned embodiments, wherein the magnesium-aluminum spinel transparent ceramic has a hardness greater than 13 GPa, a bending strength greater than 240 MPa, and a transmittance in the visible light band greater than 70%.

[0022] The present invention has the following beneficial effects:

[0023] The implementation method of the present application generates Joule heat through pulse flash discharge, which causes the raw material powder to quickly heat up and react, thereby obtaining magnesium aluminate spinel powder with a particle size as small as about 40 nm, which is used for the preparation of magnesium aluminate spinel transparent ceramics, and is beneficial to improving the mechanical properties and optical properties of magnesium aluminate spinel transparent ceramics.

[0024] By utilizing the flash Joule heat ultra-fast heating technology, magnesium-aluminum spinel powder can be synthesized within a few seconds, and in particular, the cooling speed is also very fast. Compared with the traditional synthesis method, the synthesis time is greatly reduced, the efficiency is improved, energy is saved, the cost is reduced, and it is environmentally friendly and has the prospect of large-scale industrial application; and the magnesium-aluminum spinel powder synthesized by Joule heat does not require additional ball milling or heating calcination treatment, the process is simple and easy to operate, and the powder particle size is fine and uniform, the morphology is regular, and the purity is high; the powder synthesized by the present invention has high sintering activity, and magnesium-aluminum spinel transparent ceramics with excellent performance can be obtained through low-temperature pressureless sintering and hot isostatic pressing. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 Schematic diagram of the synthesis of magnesium aluminate spinel powder by flash Joule heat.

[0027] Figure 2 This is the XRD spectrum of the magnesium aluminum spinel powder synthesized in Example 1.

[0028] Figure 3 This is the SEM photograph of the magnesium aluminum spinel powder synthesized in Example 1.

[0029] Figure 4 This is a photograph of the appearance of the magnesium-aluminum spinel transparent ceramic prepared in Example 2.

[0030] Figure 5 This is the transmittance curve of the magnesium aluminum spinel transparent ceramic prepared in Example 2. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0032] An embodiment of the present invention provides a method for synthesizing magnesium-aluminum spinel powder based on flash Joule heat, comprising: heating a mixed powder using Joule heat generated by pulse flash discharge to obtain magnesium-aluminum spinel powder, wherein the mixed powder comprises MgO powder and α-Al2O3 powder in a molar ratio of 1:(1-1.5), and the heating is followed by heat preservation and cooling.

[0033] The implementation method of the present application generates Joule heat through pulse flash discharge, which causes the raw material powder to quickly heat up and react, thereby obtaining magnesium aluminate spinel powder with a particle size as small as about 40 nm, which is used for the preparation of magnesium aluminate spinel transparent ceramics, and is beneficial to improving the mechanical properties and optical properties of magnesium aluminate spinel transparent ceramics.

[0034] Among them, the molar ratio of MgO powder and α-Al2O3 powder is related to the composition of the magnesium-aluminum spinel powder to be prepared, and is usually determined according to the molar ratio of MgO and α-Al2O3 in the chemical formula of magnesium-aluminum spinel powder MgO·nAl2O3 to determine the molar ratio of MgO powder and α-Al2O3 powder in the mixed powder.

[0035] In an optional embodiment, the heating, insulation and cooling cycles are performed 1-10 times;

[0036] And / or, the particle size of the MgO powder is below 100 nm and the purity is above 99.9%;

[0037] And / or, the particle size of the α-Al2O3 powder is below 100 nm and the purity is above 99.9%;

[0038] And / or, the preparation of the mixed powder includes: ball milling, mixing, drying and sieving MgO powder and α-Al2O3 powder in sequence to obtain the mixed powder.

[0039] The heating can be carried out multiple times, which is beneficial to the full reaction of the raw materials and avoids the agglomeration of the powder, and is beneficial to obtaining magnesium-aluminum spinel powder with fine particle size. After heating, the temperature is kept and cooled. Cooling means stopping the pulse flash discharge, cooling without external interference, interrupting the reaction, and avoiding long-term insulation that causes the powder particles to become larger and agglomerate.

[0040] Selecting raw materials with smaller particle sizes is beneficial to increasing the contact area between MgO powder and α-Al2O3 powder, facilitating a rapid reaction between the two, and obtaining magnesia-alumina spinel powder with fine particle sizes.

[0041] In an optional embodiment, the medium for ball milling is anhydrous ethanol, the grinding balls are made of alumina, the mass ratio of the grinding balls to the mixed powder is (4.5-5.5):1, the mass ratio of the mixed powder to anhydrous ethanol is (0.2:0.8) to (0.3:0.7), the ball milling method is planetary ball milling, the rotation speed is 200 to 300 r / min, and the ball milling time is 20 to 30 hours;

[0042] And / or, the drying temperature is 50° C. to 80° C., the drying time is 8 h to 12 h, and the sieving mesh size is 150 meshes.

[0043] The ball milling mixing method is conducive to the full mixing of MgO powder and α-Al2O3 powder. By adjusting the parameters of the ball milling, the mixing efficiency can be improved while ensuring uniform mixing of the raw materials.

[0044] In an optional embodiment, the voltage of the pulse flash discharge is 200V to 300V, the temperature of the insulation step is 1200°C to 1600°C, the insulation time is 0.3s to 10s, the heating rate is 1500°C / s to 4000°C / s, and the condition is vacuum or inert atmosphere.

[0045] MgO powder and α-Al2O3 powder react at 1200°C to 1600°C, with each reaction time being 0.3s to 10s. Under this condition, the reaction can be ensured to proceed quickly without causing the magnesium-aluminum spinel powder to agglomerate.

[0046] In some embodiments, if the heating condition is vacuum, the vacuum degree is generally about -0.09 MPa. If the heating condition is an inert atmosphere, the inert gas is generally argon gas, and the pressure is between -0.02 and -0.01 MPa.

[0047] An embodiment of the present invention further provides a method for preparing a magnesium-aluminum spinel transparent ceramic, comprising: molding, pressureless sintering, hot isostatic pressing and annealing the magnesium-aluminum spinel powder described in the aforementioned embodiment to obtain the magnesium-aluminum spinel transparent ceramic.

[0048] The preparation of magnesium-aluminum-spinel transparent ceramics with magnesium-aluminum-spinel powder having a fine particle size is beneficial to improving the mechanical properties and optical properties of magnesium-aluminum-spinel transparent ceramics.

[0049] In an optional embodiment, the molding method is dry pressing and then cold isostatic pressing, wherein the pressure of dry pressing is 10MPa-20MPa, the holding time is 3min-6min, and the pressure of cold isostatic pressing is 200MPa-300MPa, and the holding time is ≥10min;

[0050] And / or, the molding method is gel injection molding followed by cold isostatic pressing, wherein the gel system used for gel injection molding is a water-based AM-MABM gel system, specifically acrylamide as a monomer, methylenebisacrylamide as a cross-linking agent, ammonium persulfate as an initiator, and tetramethylethylenediamine as a catalyst; the cold isostatic pressing pressure is 200MPa to 300MPa, and the holding time is ≥10min.

[0051] In an optional embodiment, the pressureless sintering temperature is 1300° C. to 1550° C., and the time is 5 h to 15 h.

[0052] In an optional embodiment, the hot isostatic pressing is performed at a pressure of 150 MPa to 200 MPa, a temperature of 1350° C. to 1650° C., and a time of 2 h to 4 h.

[0053] The combination of pressureless sintering and hot isostatic pressing is beneficial to improving the densification of magnesium-aluminum spinel transparent ceramics, refining the grains, and improving the microstructure of magnesium-aluminum spinel transparent ceramics, which is beneficial to improving the mechanical and optical properties of magnesium-aluminum spinel transparent ceramics.

[0054] In an optional embodiment, the annealing temperature is 1100° C. to 1300° C., and the holding time is 3 h to 6 h.

[0055] Annealing under this condition is beneficial to refine the grain size, reduce internal stress, and improve the mechanical and optical properties of magnesium-aluminum spinel transparent ceramics.

[0056] An embodiment of the present invention also provides a magnesium-aluminum spinel transparent ceramic, which is prepared by the method described in any one of the aforementioned embodiments. The magnesium-aluminum spinel transparent ceramic has a hardness greater than 13 GPa, a bending strength greater than 240 MPa, and a transmittance in the visible light band greater than 70%.

[0057] The features and performance of the present invention are further described in detail below in conjunction with the examples. The model of the pulsed electro-flash reactor used in the following examples is FJH-2024APlus, from Saiyin New Material Technology Co., Ltd. The appearance and structure of the tubular reaction frame used are as shown in patent CN308075427S, from Saiyin New Material Technology Co., Ltd., and the structural schematic diagram is as shown in FIG. Figure 1 shown.

[0058] Example 1

[0059] A method for synthesizing magnesium-aluminum spinel powder based on flash Joule heat and preparing magnesium-aluminum spinel transparent ceramics using the same, wherein the chemical formula of the magnesium-aluminum spinel powder is MgO·Al2O3, specifically comprising the following steps:

[0060] Step 1: weigh 10.2g of α-Al2O3 powder and 4g of MgO powder according to the chemical formula, with a particle size of 30nm, add 71g of alumina grinding balls and 43g of anhydrous ethanol, and perform planetary ball milling at a speed of 250r / min for 24h. Then pour out the slurry, heat and dry it at 60℃ in air for 8h, and then pass it through a 150-mesh sieve to obtain a mixed powder.

[0061] Step 2: The mixed powder obtained in step 1 is placed in a quartz tube with graphite paper inside, and then placed in a tubular reaction rack. The reaction rack is then placed in a vacuum reaction box of a pulse electric flash reactor. Under a vacuum of -0.09 MPa, the pulse discharge voltage is set to 230 V. The temperature is rapidly raised to 1200° C. by pulse flash discharge, maintained for 0.5 s, and then rapidly cooled to room temperature. The discharge heating-maintaining-cooling process is cycled 10 times to obtain magnesium aluminum spinel powder. The XRD spectrum is as follows: Figure 2 As shown in the SEM images Figure 3 shown.

[0062] Step 3, the powder obtained in step 2 is first dry-pressed at a pressure of 15 MPa and maintained at pressure for 5 minutes, and then cold isostatically pressed at a pressure of 300 MPa and maintained at pressure for 15 minutes to obtain a magnesia-alumina spinel blank.

[0063] Step 4, placing the green billet obtained in step 3 into a muffle furnace, sintering it pressurelessly at 1350° C. in air for 12 hours, and then placing it into a hot isostatic pressing furnace for hot isostatic pressing at 1400° C. / 180 MPa / 4 hours.

[0064] Step 5, placing the ceramic obtained in step 4 into a muffle furnace, annealing at 1200° C. for 4 hours in air, and then double-sided polishing to obtain magnesium-aluminum spinel transparent ceramics.

[0065] Figure 2 The XRD spectrum of the powder synthesized in Example 1 is compared with the PDF#21-1152 standard card of MgAl2O4 phase, which shows that the powder is a pure phase of magnesium aluminum spinel without any second phase.

[0066] Figure 3 This is a SEM photograph of the magnesium-aluminum spinel powder synthesized in Example 1. It can be seen that the powder particles are fine, the average particle size is about 40nm, and the morphology is regular.

[0067] Example 2

[0068] A method for synthesizing magnesium-aluminum spinel powder based on flash Joule heat and preparing magnesium-aluminum spinel transparent ceramics using the same, the chemical formula of which is MgO·1.2Al2O3, comprises the following steps:

[0069] Step 1: According to the chemical formula, 18.4 g of α-Al2O3 powder and 6 g of MgO powder were weighed, with particle sizes of 40 nm and 50 nm respectively, and 122 g of alumina grinding balls and 90 g of anhydrous ethanol were added to perform planetary ball milling at a speed of 260 r / min for 24 h. The slurry was then poured out, heated and dried at 60 ° C in air for 10 h, and then sieved through a 150 mesh sieve to obtain a mixed powder.

[0070] Step 2, the mixed powder obtained in step 1 is placed in a quartz tube with graphite paper inside, placed in a tubular reaction rack, and then the reaction rack is placed in a vacuum reaction box of a pulse electro-flash reactor. Under an argon atmosphere, the pulse discharge voltage is set to 260V, and the temperature is rapidly raised to 1400°C through pulse flash discharge, maintained for 2s, and then rapidly cooled to room temperature. The discharge heating-keeping-cooling process is repeated 8 times to obtain magnesium aluminum spinel powder.

[0071] Step 3, the powder obtained in step 2 is first gel-casted using a water-based AM-MABM system, and then cold isostatically pressed at a pressure of 300 MPa for 20 minutes to obtain a magnesium-aluminum spinel blank.

[0072] Step 4, placing the green billet obtained in step 3 into a muffle furnace, sintering it pressurelessly at 1450° C. in air for 10 hours, and then placing it into a hot isostatic pressing furnace for hot isostatic pressing at 1550° C. / 190 MPa / 3 hours.

[0073] Step 5, placing the ceramic obtained in step 4 into a muffle furnace, annealing at 1200° C. for 4 hours in air, and then double-sided polishing to obtain magnesium-aluminum spinel transparent ceramics.

[0074] Figure 4 This is a photo of the appearance of the magnesium-aluminum spinel transparent ceramic prepared in Example 2. The text behind the ceramic can be clearly seen.

[0075] Figure 5 The transmittance curve of the magnesium-aluminum spinel transparent ceramic prepared in Example 2 can reach up to 85% in the visible light band.

[0076] Example 3

[0077] A method for synthesizing magnesium-aluminum spinel powder based on flash Joule heat and preparing magnesium-aluminum spinel transparent ceramics using the same, the chemical formula of which is MgO·1.5Al2O3, comprises the following steps:

[0078] Step 1: weigh 15.3g of α-Al2O3 powder and 4g of MgO powder according to the chemical formula, with an average particle size of 40nm, add 96.5g of alumina grinding balls and 75g of anhydrous ethanol, and perform planetary ball milling at a speed of 280r / min for 24h. Then pour out the slurry, heat and dry it at 70℃ in air for 10h, and then pass it through a 150-mesh sieve to obtain a mixed powder.

[0079] Step 2, the mixed powder obtained in step 1 is placed in a quartz tube with graphite paper inside, placed in a tubular reaction rack, and then the reaction rack is placed in a vacuum reaction box of a pulse electro-flash reactor. Under an argon atmosphere, the pulse discharge voltage is set to 290V, and the temperature is rapidly raised to 1550°C through pulse flash discharge, maintained for 4s, and then rapidly cooled to room temperature. The discharge heating-keeping-cooling process is repeated 8 times to obtain magnesium aluminum spinel powder.

[0080] Step 3, dry-press the powder obtained in step 2 at a pressure of 20 MPa for 5 minutes, and then cold isostatically press at a pressure of 300 MPa for 20 minutes to obtain a magnesia-alumina spinel blank.

[0081] Step 4, placing the green billet obtained in step 3 into a muffle furnace, sintering it pressurelessly at 1550° C. in air for 8 hours, and then placing it into a hot isostatic pressing furnace for hot isostatic pressing at 1600° C. / 190 MPa / 4 hours.

[0082] Step 5, placing the ceramic obtained in step 4 into a muffle furnace, annealing at 1300° C. for 4 hours in air, and then double-sided polishing to obtain magnesium-aluminum spinel transparent ceramics.

[0083] Embodiment 4:

[0084] The difference between this embodiment and embodiment 1 is that the number of cycles of step 2 is 5 times.

[0085] Comparative Example 1:

[0086] The difference between this comparative example and Example 1 is that step 2 is different: the mixed powder obtained in step 1 is loaded into a graphite mold, the graphite mold is placed in a large current reaction synthesis device, 0.05 MPa of high-purity nitrogen is filled into the large current synthesis device as a protective gas, a large current of 14 kA is directly applied to the graphite mold, the synthesis temperature is 1200°C, the heating rate is 500°C / min, the temperature is kept for 15 minutes, and the block crude product is obtained after cooling at a rate of 40°C / min; the obtained block crude product is then crushed with an agate grinding body and passed through a 50-mesh sieve, and then the sieved powder is added with 60g of alumina grinding balls and 60ml of anhydrous ethanol for wet grinding for 24 hours to obtain a slurry, the slurry is taken out and dried at 50°C under vacuum conditions for 12 hours, and then passed through a 200-mesh sieve to obtain magnesium aluminum spinel powder.

[0087] Comparative Example 2:

[0088] The difference between this comparative example and Example 1 is that the parameters of step 2 are different: the temperature is rapidly raised to 1000° C. by pulse flash discharge, and the other parameters are the same as those of Example 1.

[0089] Comparative Example 3:

[0090] The difference between this comparative example and Example 1 is that the parameters of step 2 are different: the holding time is 20s, and the other parameters are the same as those of Example 1.

[0091] The magnesium aluminum spinel transparent ceramics prepared in the examples of the present invention and the comparative examples were tested for mechanical properties and visible light transmittance.

[0092] Test method:

[0093] Hardness: Vickers hardness tester;

[0094] Bending strength: three-point bending method of universal testing machine;

[0095] Visible light transmittance: UV-visible spectrophotometer.

[0096] The performance test results of the samples are shown in Table 1. It can be seen that the magnesium-aluminum spinel transparent ceramics prepared by using the magnesium-aluminum spinel powder synthesized in the present invention have good mechanical properties and optical properties.

[0097] Table 1 Mechanical properties of the magnesium aluminum spinel transparent ceramics of the present invention and the maximum transmittance in the visible light band (390-780nm)

[0098] Hardness(GPa) Flexural strength(MPa) Transmittance % Example 1 13.7 276 83 Example 2 14.1 286 85 Example 3 14.3 292 85 Example 4 13.2 243 73 Comparative Example 1 13.1 237 80 Comparative Example 2 12.4 197 20 Comparative Example 3 13.2 239 82

[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for synthesizing magnesium-aluminum spinel powder based on flash Joule heat, characterized in that: include: The mixed powder is heated by Joule heat generated by pulse flash discharge to obtain magnesium aluminum spinel powder, wherein the mixed powder includes MgO powder and α-Al2O3 powder in a molar ratio of 1: (1-1.5), and the temperature is maintained and cooled after the heating.

2. The method for synthesizing magnesium-aluminum spinel powder based on flash Joule heat according to claim 1, characterized in that: The heating, keeping warm and cooling cycles are performed 1 to 10 times; And / or, the particle size of the MgO powder is below 100 nm and the purity is above 99.9%; And / or, the particle size of the α-Al2O3 powder is below 100 nm and the purity is above 99.9%; And / or, the preparation of the mixed powder includes: ball milling, mixing, drying and sieving MgO powder and α-Al2O3 powder in sequence to obtain the mixed powder.

3. The method for synthesizing magnesium-aluminum spinel powder based on flash Joule heat according to claim 2, characterized in that: The medium for ball milling is anhydrous ethanol, the grinding balls are made of alumina, the mass ratio of the grinding balls to the mixed powder is (4.5-5.5):1, the mass ratio of the mixed powder to anhydrous ethanol is (0.2:0.8)-(0.3:0.7), the ball milling method is planetary ball milling, the rotation speed is 200-300 r / min, and the ball milling time is 20-30h; And / or, the drying temperature is 50° C. to 80° C., the drying time is 8 h to 12 h, and the sieving mesh size is 150 meshes.

4. The method for synthesizing magnesium-aluminum spinel powder based on flash Joule heat according to claim 1, characterized in that: The pulse flash discharge is carried out under vacuum conditions or inert atmosphere, with a voltage of 200V to 300V, a temperature of the insulation step of 1200°C to 1600°C, a insulation time of 0.3s to 10s, and a heating rate of 1500°C / s to 4000°C / s.

5. A method for preparing a magnesium aluminum spinel transparent ceramic, characterized in that: include: The magnesium-aluminum spinel powder according to claim 1 is molded, pressurelessly sintered, hot isostatically pressed and annealed to obtain the magnesium-aluminum spinel transparent ceramic.

6. The method for preparing the magnesium-aluminum spinel transparent ceramic according to claim 5, characterized in that: The forming method is dry pressing first and then cold isostatic pressing, wherein the pressure of dry pressing is 10MPa-20MPa, the holding time is 3min-6min, and the pressure of cold isostatic pressing is 200MPa-300MPa, the holding time is ≥10min; And / or, the molding method is gel injection molding followed by cold isostatic pressing, wherein the gel system used for gel injection molding has acrylamide as a monomer, methylenebisacrylamide as a cross-linking agent, ammonium persulfate as an initiator, and tetramethylethylenediamine as a catalyst; the cold isostatic pressing pressure is 200MPa to 300MPa, and the holding time is ≥10min.

7. The method for preparing the magnesium-aluminum spinel transparent ceramic according to claim 5, characterized in that: The pressureless sintering temperature is 1300° C. to 1550° C., and the sintering time is 5 h to 15 h.

8. The method for preparing the magnesium-aluminum spinel transparent ceramic according to claim 5, characterized in that: The hot isostatic pressing has a pressure of 150 MPa to 200 MPa, a temperature of 1350° C. to 1650° C., and a time of 2 h to 4 h.

9. The method for preparing the magnesium-aluminum spinel transparent ceramic according to claim 5, characterized in that: The annealing temperature is 1100° C. to 1300° C., and the holding time is 3 h to 6 h.

10. A magnesium aluminum spinel transparent ceramic, characterized in that: Prepared by the method described in any one of claims 5 to 9, the magnesium aluminum spinel transparent ceramic has a hardness greater than 13 GPa, a bending strength greater than 240 MPa, and a transmittance in the visible light band greater than 70%.

Citation Information

Cited By

  • Method for removing heavy metals in waste incineration fly ash based on flash Joule heating technology

    CN120619034A